Unveiling the power of social influence: how functional, emotional, and social values drive Pilates participation through an extended TPB model - Kim, Sukkyu; Jeong, Yunduk; Jung, Youngsu (Frontiers in Psychology, 2025)
PurposeThis study investigates how functional, emotional, and social values shape Pilates participants’ attitudes and behavioral intentions within an Extended Theory of Planned Behavior (ETPB) framework.MethodA survey was conducted with 288 Pilates participants, and structural equation modeling was employed to analyze the relationships among perceived value, attitude, subjective norms, perceived behavioral control, and behavioral intention.ResultsThe findings indicate that functional and social values positively influence attitudes, whereas emotional value has no significant effect. Moreover, subjective norms exert the strongest influence on behavioral intention, highlighting the importance of social factors in Pilates participation.Discussion/conclusionThis study underscores the role of perceived value in shaping attitudes and confirms the dominant impact of subjective norms on behavioral intention. The findings offer theoretical contributions by refining the ETPB model and provide practical insights for enhancing engagement in Pilates programs.Originality/valueThis study contributes to the literature by applying an ETPB model to the context of Pilates, incorporating perceived value as an additional factor. It challenges the traditional emphasis on attitude as the primary predictor of behavioral intention by highlighting the dominant role of subjective norms. These insights offer a more nuanced understanding of the factors driving Pilates participation and provide practical implications for developing strategies to enhance engagement and retention in Pilates programs.